Soluble intracellular adhesion molecule, M30 and M65 as serum markers of disease activity and prognosis in cholestatic liver diseases. Issue 13 (28th February 2014) - Denk, Gerald; Omary, Ahmed‐Jawid; Reiter, Florian Paul; Hohenester, Simon; Wimmer, Ralf; Holdenrieder, Stefan; Rust, Christian
Abstract : Aim: Hepatic apoptosis is involved in the pathogenesis of immune‐mediated liver diseases such as autoimmune hepatitis (AIH), primary biliary cirrhosis (PBC) and primary sclerosing cholangitis (PSC). The aim of our study was to quantify distinct markers of apoptosis in sera of patients with AIH, PBC and PSC, and to evaluate correlation with markers of disease activity and prognosis. Methods: Sera of patients with AIH, PBC and PSC, and of healthy controls were collected and distinct cell death markers were quantified using a bead‐based multiplex enzyme linked immunosorbent assay (soluble intracellular adhesion molecule [sICAM], macrophage migration inhibitory factor [MIF], soluble Fas [sFas], plasminogen activator inhibitor 1 [PAI‐1]) or single enzyme‐linked immunosorbent assays (DNAse, M30, M65). Results: In comparison with healthy controls, the apoptotic markers sFas, sICAM (only in PSC patients), M30 and the cell death marker M65 were substantially elevated in sera of patients with immune‐mediated liver diseases, whereas DNAse activity was reduced. Interestingly, patients with advanced PSC presented with higher levels of sICAM, M30 and M65 than patients with mild PSC. Regression analysis revealed correlations between serum levels of sICAM, M30 and M65 with the Mayo Risk Score for PSC, and of M65 with the Mayo Risk Score for PBC. Conclusion: Concentrations of the serum markers of apoptosis sFas and M30 and of the marker of total cell death M65 are elevated in patients with immune‐mediated liver diseases, whereas activity of DNAse is reduced. In patients with PSC, sICAM, M30 and M65 may serve as indicators for disease activity and prognosis.